WritLarge: Ink Unleashed by Unified Scope, Action, & Zoom - Xia, Haijun; Hinckley, Ken; Pahud, Michel; Tu, Xiao; Buxton, Bill (Proceedings of the 2017 CHI Conference on Human Factors in Computing Systems (CHI '17), 2017)
WritLarge is a freeform canvas for early-stage design on electronic whiteboards with pen+touch input. The system aims to support a higher-level flow of interaction by ‘chunking’ the traditionally disjoint steps of selection and action into unified selection-action phrases. This holistic goal led us to address two complementary aspects: SELECTION, for which we devise a new technique known as the Zoom-Catcher that integrates pinch-to-zoom and selection in a single gesture for fluidly selecting and acting on content; plus: ACTION, where we demonstrate how this addresses the combined issues of navigating, selecting, and manipulating content. In particular, the designer can transform select ink strokes in flexible and easily-reversible representations via semantic, structural, and temporal axes of movement that are defined as conceptual ‘moves’ relative to the specified content. This approach dovetails zooming with lightweight specification of scope as well as the evocation of context-appropriate commands, at-hand, in a location-independent manner. This establishes powerful new primitives that can help to scaffold higher-level tasks, thereby unleashing the expressive power of ink in a compelling manner.
Honorable Mention